DISCOVERING ONE'S OWN KNOWLEDGE: A CRITICAL REVIEW AND OPPORTUNITIES FOR IMPLEMENTING DISCOVERY LEARNING IN THE DIGITAL ERA - Nurzaelani, Mohammad Muhyidin; Muslim, Suyitno; Khaerudin (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
21st century education demands a learning approach that not only transmits knowledge but also encourages students to actively construct their own understanding through direct involvement and critical thinking. In this context, the discovery learning approach becomes increasingly relevant. Discovery learning was first popularized by Jerome S. Bruner in the 1960s as a learning approach that emphasizes the active process of discovering concepts and principles through exploration and direct experience. This approach is rooted in the theory of constructivism which believes that knowledge is constructed through active interaction with the environment and the cognitive involvement of learners. This study adopts a qualitative approach with a library research type. The main objectives of this study are to examine in depth the principles of discovery learning, explore the possibilities of its application in the digital era, and explore the challenges and limitations in its application.